Measurement of the CP-violating phase [phi]s from Bs0→J/[psi]π+π− decays in 13 TeV pp collisions - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2019)
Decays of Bs0 and B‾0s mesons into J/ψπ+π− final states are studied in a data sample corresponding to 1.9 fb−1 of integrated luminosity collected with the LHCb detector in 13 TeV pp collisions. A time-dependent amplitude analysis is used to determine the final-state resonance contributions, the CP-violating phase ϕs=−0.057±0.060±0.011 rad, the decay-width difference between the heavier mass Bs0 eigenstate and the B0 meson of −0.050±0.004±0.004 ps−1, and the CP-violating parameter |λ|=1.01−0.06+0.08±0.03, where the first uncertainty is statistical and the second systematic. These results are combined with previous LHCb measurements in the same decay channel using 7 TeV and 8 TeV pp collisions obtaining ϕs=0.002±0.044±0.012 rad, and |λ|=0.949±0.036±0.019.
Im Titel ist der Buchstabe "s" tiefgestellt
Im Titel ist die Zahl "0" sowie die Zeichen "+" und "-" hochgestellt
Im Titel sind [phi] und [psi] als griechische Buchstaben dargestellt
Gesehen am 24.10.2019
*LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. D'Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 822 weitere Personen]